2022
DOI: 10.1210/clinem/dgac332
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Homeostasis in Obesity-related Hypertriglyceridemia

Abstract: Context The prevalence of obesity and hypertriglyceridemia is an alarming worldwide health issue. Mitochondria play a central role in these disorders as they control cell metabolism. Objective The aim of the present study was to characterize mitochondrial homeostasis in subcutaneous and visceral adipose tissue (SAT and VAT) in grade III obese patients with and without hypertriglyceridemia. Moreover, this study presents the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies showed that ketone bodies are potent inducers of mitochondrial biogenesis by upregulating the expression of the transcription factor, PGC1α 36 , 37 . Because mitochondrial homeostasis including biogenesis and function is key in regulating lipid metabolism 38 , we assessed whether impaired ketogenesis affected mitochondrial homeostasis in Hmgcs2 ΔLiv mice. We found no difference in the mRNA expression of Pgc1α, Nrf2, and various other mitochondria-associated genes such as Atp6, Cox1, and Nd4 in Hmgcs2 ΔLiv mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that ketone bodies are potent inducers of mitochondrial biogenesis by upregulating the expression of the transcription factor, PGC1α 36 , 37 . Because mitochondrial homeostasis including biogenesis and function is key in regulating lipid metabolism 38 , we assessed whether impaired ketogenesis affected mitochondrial homeostasis in Hmgcs2 ΔLiv mice. We found no difference in the mRNA expression of Pgc1α, Nrf2, and various other mitochondria-associated genes such as Atp6, Cox1, and Nd4 in Hmgcs2 ΔLiv mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…114 As mitochondria play an essential role in human metabolism and energy homeostasis, mitochondrial dysfunction is associated with the pathophysiology of metabolic diseases. [115][116][117] It is noteworthy that exercise training is able to induce beneficial mitochondrial adaptations, including enhanced mitochondrial content, protein synthesis, oxidative capacity, or biogenesis, as well as the more efficient removal of dysfunctional/damaged mitochondria, with derived benefits in metabolic health. 118,119 Indeed, these adaptations appear to be exercise modality dependent 120 and may also be affected by other factors, such as training volume or intensity.…”
Section: Mitochondrial Fitnessmentioning
confidence: 99%
“…Furthermore, beyond their bioenergetic function, mitochondria are a hub for the generation of biosynthetic precursors, maintenance of redox balance, and management of metabolic waste 114 . As mitochondria play an essential role in human metabolism and energy homeostasis, mitochondrial dysfunction is associated with the pathophysiology of metabolic diseases 115–117 . It is noteworthy that exercise training is able to induce beneficial mitochondrial adaptations, including enhanced mitochondrial content, protein synthesis, oxidative capacity, or biogenesis, as well as the more efficient removal of dysfunctional/damaged mitochondria, with derived benefits in metabolic health 118,119 .…”
Section: Mechanisms Behind the Effects Of Time‐based Exercise On Meta...mentioning
confidence: 99%